Analysis of Photocopy Service Queue System in “Sustainable Photocopy” Using The FIFO Queue Method - Wira Yudha Nuswantoro; Erwan Adi Saputro; Mutiara Mei Susanti; Yekti Condro Winursito; Hafid Syaifullah (Tibuana, 2023)
Photocopying services are services that are always sought by students, students, teachers, lecturers, and even office people for the need to duplicate school assignments, theses, document files, etc. "Sustainable" Photocopy Services are rarely empty of customers. And for a certain time, there are a lot of customers from "Sustainable" Photocopies. With this research, we can find out whether the queuing system at Sustainable Photocopy Services is optimal, and with the analysis of this queuing system by calculating the queuing formula it can be seen the call arrival rate, employee utility level, the average number of customers to be served, the number of customers in the system, the number of customers in the queue, the average time in the queue, the average time in the system, and the probability of waiting.